ORGANIZATION OF INTERNET MARKETING IN THE SPHERE OF B2B - Marjona Holbozorova; Mukhtasar Ziyaeva (Journal Park Publishing, 2023)
The article discusses the organization of Internet marketing in the field of B2B, an analysis of the development and distribution trends is made.
Keywords: internet marketing, economy, B2B sphere, company, internet resources, statistics, efficiency, growth dynamics.